2011
DOI: 10.1158/1541-7786.mcr-10-0407
|View full text |Cite
|
Sign up to set email alerts
|

MGMT Is a Molecular Determinant for Potency of the DNA-EGFR–Combi-Molecule ZRS1

Abstract: To enhance the potency of current EGFR inhibitors, we developed a novel strategy that seeks to confer them an additional DNA damaging function, leading to the design of drugs termed combi-molecules. ZRS1 is a novel combi-molecule that contains an EGFR tyrosine kinase targeting quinazoline arm and a methyltriazenebased DNA damaging one. We examined its effect on human tumor cell lines with varied levels of EGFR and O6-methylguanine DNA methyltransferase (MGMT). ZRS1 was more potent than the clinical methylating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…The combi-molecule strategy aims to the vectorization of anticancer drugs to target specific tissues is also a promising method to design highly effective, non-toxic and useful hybrids. Compound 97 is a hybrid connecting also aromatic nitrogen mustards (40)(41)(42) and tyrosine that was designed to mimic the estradiol nucleus [55]. Compound 97 exhibits antiproliferative activity in the M range on prostate, breast, ovarian and uterine cancer cell lines and was slightly more active than chlorambucil (41).…”
Section: Combi-molecules In the Aim To Target Specific Biological Tismentioning
confidence: 99%
“…The combi-molecule strategy aims to the vectorization of anticancer drugs to target specific tissues is also a promising method to design highly effective, non-toxic and useful hybrids. Compound 97 is a hybrid connecting also aromatic nitrogen mustards (40)(41)(42) and tyrosine that was designed to mimic the estradiol nucleus [55]. Compound 97 exhibits antiproliferative activity in the M range on prostate, breast, ovarian and uterine cancer cell lines and was slightly more active than chlorambucil (41).…”
Section: Combi-molecules In the Aim To Target Specific Biological Tismentioning
confidence: 99%
“…EGFR is one of the most investigated receptor tyrosine kinases in the context of DNA repair. Through the mitogen-activated protein kinase (MAPK) pathway, EGFR activation leads to expression of DNA repair genes [ 11 ] and through the phosphatidylinositol-3 kinase (PI3K) pathway, it exerts an antiapoptotic effect [ 12 ]. Based on the premise that activation of EGFR leads to induction of DNA repair proteins such as X-ray repair cross-complementing protein 1 (XRCC1) and excision repair cross-complementation group 1 (ERCC1), our group embarked onto the design of drugs termed “combi-molecules” that can induce a tandem targeting of EGFR and DNA and demonstrated that indeed the latter dual targeted molecules could down-regulate XRCC1 and ERCC1 through their EGFR inhibitory arm and inducing high levels of DNA strand breaks through their DNA alkylating arm [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Promoter methylation of MGMT is now clinically used in the management of glioblastoma multiforme [ 13 ]. Importantly, questions relative to the association between EGFR activation and MGMT-mediated repair has been molecularly and pharmacologically addressed by our group [ 12 ]. Using double arm combi-molecules designed to down-regulate EGFR and methylate DNA, we demonstrated that MGMT expression was uncoupled with down-regulation of EGFR signaling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A549 (ATCC® CCL-185™), DU145 (ATCC® HTB-85™), and A427 (ATCC® HTB-53™), was purchased from ATCC. A427-MGMT was obtained by stable transfection of A427 with MGMT viral vector in our lab [ 26 ]. All cell lines were maintained in in DMEM media from Wisent Bio Products.…”
Section: Methodsmentioning
confidence: 99%